Cascade search for HSV-1 combinatorial drugs with high antiviral efficacy and low toxicity - Ding X (Dove Medical Press, 2012)
Xianting Ding1, David Jesse Sanchez2,3, Arash Shahangian2, Ibrahim Al-Shyoukh1,4, Genhong Cheng2, Chih-Ming Ho11Department of Mechanical and Aerospace Engineering, UCLA, Los Angeles, CA, USA; 2Department of Microbiology, Immunology, and Molecular Genetics, UCLA, Los Angeles, CA, USA; 3Department of Pharmaceutical Sciences, College of Pharmacy, Western University of Health Sciences, Pomona, CA, USA; 4Molecular and Medical Pharmacology Department, David Geffen School of Medicine, UCLA, Los Angeles, CA, USABackground: Infectious diseases cause many molecular assemblies and pathways within cellular signaling networks to function aberrantly. The most effective way to treat complex, diseased cellular networks is to apply multiple drugs that attack the problem from many fronts. However, determining the optimal combination of several drugs at specific dosages to reach an endpoint objective is a daunting task.Methods: In this study, we applied an experimental feedback system control (FSC) method and rapidly identified optimal drug combinations that inhibit herpes simplex virus-1 infection, by only testing less than 0.1% of the total possible drug combinations.Results: Using antiviral efficacy as the criterion, FSC quickly identified a highly efficacious drug cocktail. This cocktail contained high dose ribavirin. Ribavirin, while being an effective antiviral drug, often induces toxic side effects that are not desirable in a therapeutic drug combination. To screen for less toxic drug combinations, we applied a second FSC search in cascade and used both high antiviral efficacy and low toxicity as criteria. Surprisingly, the new drug combination eliminated the need for ribavirin, but still blocked viral infection in nearly 100% of cases.Conclusion: This cascade search provides a versatile platform for rapid discovery of new drug combinations that satisfy multiple criteria.Keywords: drug combination, HSV-1, combinatorial drug optimization, feedback system control, FSC, drug screening